Computer Aided Platform For Teaching Physical Geography: A Case Study Of Kigezi High School. - Tumukunde, Pakarasio (Kabale University, 2024)
Computers have become an important tool for keeping databases, filing systems, and track records. It has made record-keeping much easier than it ever was. It has made data analysis extremely easy, and it can be done with a single click of the mouse unlike the traditional way of teaching which needs a lot of time to read books . While using CAI as an instructional way of teaching students are more interested in reading their lessons. The purpose of this was to develop a computer-aided platform for teaching Physical geography at Kigezi High School.